Banks and Monetary Shocks in Emerging Markets : How Far Can We Go with the "Credit View"? - Catao, Luis (IMF Working Papers; Working Paper, 2000)
This paper examines the propagation of monetary shocks in a two-good optimizing macromodel where domestic banking activity is costly and the non-tradable sector is highly dependent on domestic bank credit, as in most emerging market economies. The model develops the Bernanke-Blinder 'credit view' of the monetary transmission mechanism along classical lines, with no Keynesian rigidities being imposed and the only sources of 'imperfection' arising from deposit and credit-in-advance constraints. Using numerical simulations, we show that such a relatively simple model goes a long way toward explaining some key 'stylized facts' of recent financial crises.